2010
DOI: 10.1149/1.3487559
|View full text |Cite
|
Sign up to set email alerts
|

Enablement and Optimization of SiGe HBTs for Extreme Environment Electronics

Abstract: One of the remarkable characteristics of SiGe HBT is the ability to operate over a wide temperature range, from as low as sub 1K [1], to as high as over 400 K. This, together with excellent total dose radiation tolerance, makes it very attractive for implementing space electronics that can operate over a wide temperature range in presence of radiation as found in space missions [2].To enable such extreme designs, we have been recently developing SiGe HBT compact model as well as TCAD models that can function f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Moreover, it can be concluded that when the incidence is from the emitter center, the device is particularly susceptible to SEE. This phenomenon can be attributed to the fact that when an incident occurs from the emitter center, the incident track passes not only through the larger collector/substrate (CS) junction, which is the most sensitive position of the device, [20,21] but also through all electrode areas of the device. As a result, a significant potential collapse occurs, causing the electron-hole pairs to be quickly collected by drift under the action of the electric field to form a large transient current peak as shown in Figs.…”
Section: Setting Of Experimental Conditionsmentioning
confidence: 99%
“…Moreover, it can be concluded that when the incidence is from the emitter center, the device is particularly susceptible to SEE. This phenomenon can be attributed to the fact that when an incident occurs from the emitter center, the incident track passes not only through the larger collector/substrate (CS) junction, which is the most sensitive position of the device, [20,21] but also through all electrode areas of the device. As a result, a significant potential collapse occurs, causing the electron-hole pairs to be quickly collected by drift under the action of the electric field to form a large transient current peak as shown in Figs.…”
Section: Setting Of Experimental Conditionsmentioning
confidence: 99%